„Civitas mensura” – obywatel miarą wszechrzeczy. Emancypacyjny i upodmiotawiający wymiar obywatelskiego humanizmu - Juchacz, Piotr W. (Filozofia Publiczna i Edukacja Demokratyczna, 2017)
The consideration of emancipatory and empowering dimension of civic humanism is the chief concern of the article. In the first part there are recalled classical Protagorean sources of European humanism with a special attention to its civic dimension. In the second part I analyse points 3 and 4 of The Amsterdam Declaration 2002 dedicated to the democratic political system. In the last part I propose and develop a thesis that co-participation of citizens in exercising of all three powers in deliberative democratic system – the legislative power (participation in the law-making processes), the executive (participation in creation and realisation of public policies) and the judicial (participation in the system of exercising justice as lay judges) - constitutes the foundation of contemporary humanism as civic activity.